A polyoxometalate–organic supramolecular nanotube with high chemical stability and proton-conducting properties. Issue 11 (23rd December 2014) - Cao, Gao-Juan; Liu, Jing-Dong; Zhuang, Ting-Ting; Cai, Xiu-Hong; Zheng, Shou-Tian
Abstract : A novel polyoxometalate–organic supramolecular nanotube has been created, which has exceptional stability and proton-conducting properties. Abstract : The use of 1 H -1, 2, 4-triazole-3-thiol (H2 trzS) has led to a rare inorganic–organic hybrid supramolecular nanotube built from novel Ni5 -substituted polyoxotungstates, which presents interesting structural characteristics, high chemical stability, and proton-conducting properties.